Revealing Student Approaches Toward Engineering Problems in an LA-supported Fluid Mechanics Course - Gallegos, Hernan. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Kristen Wendell.; Committee: Chris Rogers, and Julia Gouvea.; Keywords: Mechanical engineering, and Education.